High incidence of SHOX anomalies in individuals with short stature. Issue 9 (5th April 2006) - Huber, C; Rosilio, M; Munnich, A; Cormier-Daire, V
Abstract : Objective: To study the SHOX gene and the PAR1 region in individuals with short stature. Methods: The study involved 56 cases of dyschondrosteosis and 84 cases of idiopathic short stature (ISS). The study was designed to determine the following: the prevalence of SHOX anomalies in ISS; the frequency of Madelung deformity in individuals with SHOX anomalies; and the value of a family history of short stature in deciding whether to test for the SHOX gene. Results: 54 SHOX anomalies were observed, including 42 (68%) in the dyschondrosteosis group and 12 (15%) in the ISS group. The high frequency of SHOX anomalies in the ISS group can be explained by the large proportion of boys in this group, reflecting the difficulty in diagnosing dyschondrosteosis in young boys. Clinical evidence of Madelung deformity in six parents of ISS individuals emphasised the importance of family evaluation. Among the 54 SHOX anomalies, 33 PAR1 deletions were identified encompassing the SHOX gene (62%), one partial intragenic deletion (2%), nine deletions located downstream of the SHOX gene (16%), and 11 point mutations (20%). Conclusions: These data emphasise the value of using microsatellite markers located within and downstream of the SHOX gene.